Media Pembelajaran E-comic Berbasis Problem Based Learning Berbantuan Desmos untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis - Prayoga, Ilhan N/a; N/a, Sumliyah N/a; Rohaeti, Titi N/a (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
The issue is that in the age of civilization 5.0, there aren't many options for learning, which makes it harder to comprehend math classes especially those involving straight line equations where learning ought to be participatory but isn't. The goal of this project is to develop straight line equation learning resources based on the Desmos website. In order to determine the viability and student reactions, research and development uses the ADDIE approach (Analyze, Design, Development, Implementation, and Evaluation). Neutral votes were removed from the Likert scale during data collection. Using purpose sampling procedures with 35 class VIII D students at SMP Negeri 1 Sumber, the applicability of the learning medium will be confirmed by one media expert, one language expert, one content expert, teacher replies, and student answers. Using the Desmos website, this project creates an interactive e-comic learning media product to help students solve mathematics problems in class VIII straight line equations. Based on the findings of the three validators' assessments, the learning media's feasibility received a total average score of 45.3, a feasibility percentage of 75%, and the "Worthy" category, meaning that the creation of this math learning media was deemed theoretically and conceptually feasible. Students' reaction to learning material, on the other hand, was favorable, scoring 86.37% and placing them in the "Very Good" category.